The Role of Corruption in the Implementation of Environmental Regulations - Özpolat, Asli; Ozsoy, Ferda Nakipoglu (Problemy Ekorozwoju, 2024)
The necessity for politicians to take action to prevent environmental pollution and combat environmental pollution and corruption is made clear by the rise in environmental pollution and corruption that results from growing economic activity and development in emerging countries. The correlation between economic growth, corruption, and environmental harm has been studied for groupings of high-income emerging countries for this reason. The inverted U-shaped correlation between economic growth and environmental pollution is valid for MIST but not for BRCS because of empirical studies taking cross-section dependency into account and assessing the long-term relationship. Additionally, corruption has been demonstrated to worsen environmental contamination.